Gerakan Lingkungan Yayasan Borneo Urban Lab Pada Masyarakat Tepian Sungai Di Kota Banjarmasin - Aditya, Dimas Anggi Putra; Hidayah, Sri (Program Studi Sosiologi, FISIP ULM, 2024)
ABSTRACT The level of participation of the people of Banjarmasin City in maintaining the cleanliness and sustainability of the river is still very low. This study aims to understand and illustrate the movement of a local organization that involves riverbank communities in efforts to care for the environment. This research uses a qualitative research approach with a case study research type, this research seeks to provide a detailed description of how the Borneo Urban Lab Foundation involves and influences riverbank communities to take an active role in environmental conservation. The data collection technique used in-depth interviews with the Borneo Urban Lab team, direct observation of community activities and relevant documentation. This approach plays an important role in capturing the breadth of Borneo Urban Lab's efforts and their impact on community attitudes and behaviors for environmental awareness. The findings of this study highlight the effectiveness of the Borneo Urban Lab Foundation in implementing the environmental care movement among riverside communities in Banjarmasin. Through a variety of activities such as providing education about environmental care, a week-long litter-free challenge,